Multidisciplinary approach in the clinical and laboratory investigation of a suspected case for anaplastic lymphoma associated with breast prosthesis - Vieira, René Aloisio da Costa; Oliveira-Junior, Idam de; Santos, Luciana da Fonseca; Watanabe, Ana Paula Uema; Alves, Wilson Eduardo Furlan Matos; Neder, Luciano (Mastology, 2020)
Introduction: Breast implant-associated anaplastic large cell lymphoma (BIA-ALCL) is a rare subtype of CD30-positive and ALKnegative (anaplastic lymphoma kinase) T cell lymphoma, which can develop in the pericapsular fibrous tissue and the late seromas around breast implants. If BIA-ALCL is suspected, an adequate diagnostic flow is essential. Materials and methods: A flowchart of the procedures performed in the diagnostic investigation is discussed, associating a clinical case, and conducting a review on the topic. Results: In the assessment of late and recurrent periprosthetic seromas, prior communication from the surgeon and the pathologist is essential, aiming at the adequate collection and storage of the aspirated material. The material must be promptly fractionated for microbiological assessment by culture, immediate or transoperative cytologic assessment, immunophenotyping by flow cytometry (10 mL), direct cytopathological examination, and obtaining cell block material (50 mL). For flow cytometry, the material must be sent fresh, 70% alcohol or 10% buffered formalin can be added for the other procedures. If it is impossible to send the aspirated fluid to the laboratory in less than six hours, it can be temporarily stored in a refrigerator at 4°C. Immunophenotyping should be extensive, always assessing the expression of CD30 and ALK, regardless of cytological aspects. In cases of late and recurrent seromas in which BIA-ALCL is considered, even if initially discarded, it is suggested to perform capsulectomy with the removal of the prosthesis or careful clinical and laboratory monitoring. Conclusion: The diagnostic flowchart is essential, aiming at false-negative tests.